A Case Of Periradicular Surgery: Apicoectomy And Obturation Of The Apex - Aws Hashim Ali Al-Kadhim; Sarah Taha Yousif Al-Ani; Syatirah Najmi Abdullah; Nalisha Mohamad Ramli (Japan University of Health Sciences & Japan International Cultural Exchange Foundation, 2024)
International Medical Journal Volume 30 Issue 1 Page (51-53)